PENGARUH LITERASI KEUANGAN SYARIAH, AKTIVITAS GALERI INVESTASI SYRIAH, MODAL MINIMAL, DAN RELIGIUSITAS TERHADAPMINAT INVESTASI MAHASISWA DI PASAR MODAL SYARIAH - Mohammad Sof'an (JINGJI : Jurnal Ekonomi, Bisnis dan Manajemen, 2023)
The purpose of this study is to measure and determine the effect of Islamic financial literacy, ShariaInvestment Gallery (GIS) activities, minimum capital, and religiosity on student interest in investingin the Islamic capital market. This research uses mixed method research (quantitative research andqualitative research). The population used is students who are registered as investment accountmakers in 2020 s.d. 2021 through the Sharia Investment Gallery of the Nahdlatul Ulama IslamicUniversity (UNISNU) Jepara, totaling 467 students. Sampling based on non-probability samplingwith the number of samples using simple random sampling technique with the calculation of theSlovin formula, obtained 82 respondents. Data obtained from observations, questionnaires, andindepth interviews.